U.S. Foreign Policy Towards North Korea - Husenicova, Lucia (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
The U.S. relations to Democratic People’s Republic of Korea (DPRK) are since the end of the Cold War revolving around achieving a state of nuclear free Korean peninsula. As non-proliferation is a long term of American foreign policy, relations to North Korea could be categorized primarily under this umbrella. However, the issue of North Korean political system also plays role as it belongs to the other important, more normative category of U.S. foreign policy which is the protection of human rights and spreading of democracy and liberal values. In addition, the North Korean issue influences U.S. relations and interests in broader region of Northeast Asia, its bilateral alliances with South Korea (Republic of Korea, ROK) and Japan as well as sensitive and complex relations to People’s Republic of China. As the current administration of president Donald J. Trump published its National security strategy and was fully occupied with the situation on Korean peninsula in its first year, the aim of the paper is to analyse the changes in evolution of U.S. North Korean policy under last three administrations, look at the different strategies adopted in order to achieve the same aim, the denuclearization. The paper does not provide a thorough analysis, neither looks at all documents adopted and presented in the U.S. or within the U.N. It more focuses on the general principles of particular strategies, most significant events in mutual relations as recorded by involved governmental officials and also weaknesses of these strategies as none has achieved desirable result. In conclusion, several options for current administration are drawn, however all of them require significant compromises and could be accompanied with series of setbacks dangerous for regional stability and U.S. position in the region.